In-situ X-ray tomography of wear: a feasibility study - Aleksejev, J; Lim, Y; Huber, J; Hofman, F; Marrow, TJ (Elsevier, 2020)
Wear experiments using annular contacts were carried out to investigate the possibility of imaging wear scars and wear debris beds in-situ. Samples made of 6082T6 aluminium alloy were subjected to unidirectional wear under different conditions with the sample elements then locked in contact to preserve the end-of-wear condition. Post-wear 3D morphology was successfully imaged in-situ using X-ray tomography, with total depth of the wear scar, surface primary-profile roughness and real area of contact also obtained. This study is a proof-of-concept, illustrating the utility of tomography for studying wear, without the need to disassemble the contact or disturb the debris bed and serves as a starting point for a new approach to the investigation of wear phenomena.